Sentinel nodes identified by computed tomography-lymphography accurately stage the axilla in patients with breast cancer - Motomura, Kazuyoshi (BioMed Central, 2013)
BACKGROUND: Sentinel node biopsy often results in the identification and removal of multiple nodes as sentinel nodes, although most of these nodes could be non-sentinel nodes. This study investigated whether computed tomography-lymphography (CT-LG) can distinguish sentinel nodes from non-sentinel nodes and whether sentinel nodes identified by CT-LG can accurately stage the axilla in patients with breast cancer. METHODS: This study included 184 patients with breast cancer and clinically negative nodes. Contrast agent was injected interstitially. The location of sentinel nodes was marked on the skin surface using a CT laser light navigator system. Lymph nodes located just under the marks were first removed as sentinel nodes. Then, all dyed nodes or all hot nodes were removed. RESULTS: The mean number of sentinel nodes identified by CT-LG was significantly lower than that of dyed and/or hot nodes removed (1.1 vs 1.8, p <0.0001). Twenty-three (12.5%) patients had ≥2 sentinel nodes identified by CT-LG removed, whereas 94 (51.1%) of patients had ≥2 dyed and/or hot nodes removed (p <0.0001). Pathological evaluation demonstrated that 47 (25.5%) of 184 patients had metastasis to at least one node. All 47 patients demonstrated metastases to at least one of the sentinel nodes identified by CT-LG. CONCLUSIONS: CT-LG can distinguish sentinel nodes from non-sentinel nodes, and sentinel nodes identified by CT-LG can accurately stage the axilla in patients with breast cancer. Successful identification of sentinel nodes using CT-LG may facilitate image-based diagnosis of metastasis, possibly leading to the omission of sentinel node biopsy.